2020
DOI: 10.7554/elife.51261
|View full text |Cite
|
Sign up to set email alerts
|

The evolution of the vestibular apparatus in apes and humans

Abstract: Phylogenetic relationships among extinct hominoids (apes and humans) are controversial due to pervasive homoplasy and the incompleteness of the fossil record. The bony labyrinth might contribute to this debate, as it displays strong phylogenetic signal among other mammals. However, the potential of the vestibular apparatus for phylogenetic reconstruction among fossil apes remains understudied. Here we test and quantify the phylogenetic signal embedded in the vestibular morphology of extant anthropoids (monkeys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
40
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 23 publications
(46 citation statements)
references
References 88 publications
6
40
0
Order By: Relevance
“…Overall, these studies demonstrate that the morphology of the bonylabyrinth is an ideal source of information for addressing questions about thelocomotion, phylogenetic relationships and taxonomy of extant and fossil primates. One question of fundamental interest is how the bony labyrinthine morphology changed over the course of anthropoid evolution (see also Urciuoli et al, 2020). Here we emplace key fossil hominoid primates from the Mio–Plio–Pleistocene within the extant species morphospace in order to clarify the evolutionary patterns that characterize the hominid (great ape and human) clade in more detail than currently known (Spoor et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Overall, these studies demonstrate that the morphology of the bonylabyrinth is an ideal source of information for addressing questions about thelocomotion, phylogenetic relationships and taxonomy of extant and fossil primates. One question of fundamental interest is how the bony labyrinthine morphology changed over the course of anthropoid evolution (see also Urciuoli et al, 2020). Here we emplace key fossil hominoid primates from the Mio–Plio–Pleistocene within the extant species morphospace in order to clarify the evolutionary patterns that characterize the hominid (great ape and human) clade in more detail than currently known (Spoor et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Differences in volumetric proportions of the SCs have been related to locomotor adaptations, because they directly affect the sensitivity and steadiness of the SCs in response to angular accelerations (5,56). Hence, the moderately stout SCs of the LCA of crown hominids indicate that it showed a slow type of locomotion, which was present, to a large extent, also in the LCA of crown hominoids, as previously inferred based on the size of the SC radius alone (41).…”
Section: Discussionmentioning
confidence: 75%
“…Allometric regressions of SC volume vs. length were performed separately for hominoids and the rest of anthropoids included in the sample (Fig. 2a; measurements for the dryopiths are given in Supplementary Table 1) because it has been previously shown that the former display an allometric grade shift toward relatively higher volumes at a comparable length once size-scaling effects have been taken into account (5), with only minimal overlap. Hispanopithecus falls above the hominid regression line, while Rudapithecus is situated more (RUD 77) or less (RUD 200) below the line, close to Nacholapithecus, but in all cases within the range of extant hominids and well above the regression line of other anthropoids (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations